ANALISIS KUALITAS LAYANAN PT. TELKOM KANDATEL MAKASSAR - Fitriany Fitriany (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The aim of the study was to analyze the quality of interaction, quality of physical environment, and quality of product affecting the customer's satisfaction of PT Telkom Kandatel in Makassar and the most dominant service quality affecting the customer's satisfaction. The analysis used in the study was descriptive and multiple linear regression. The results of the study indicate that quality of interaction, quality of physical environment, and quality of product simultaneously affect the customer's satisfaction. Partially, quality of product is the most dominant factor affecting the customer's satisfaction of PT. Telkom Kandatel in Makassar.